Feasibility of a videoconferencing-based parent-mediated intervention: a mixed-method pilot study - Geoffray, Marie-Maude; Bourgeois-Mollier, Maeva; Maleysson-Baste, Maud; Gallifet, Natacha; Dochez, Sara; Bonis, Gaelle; Jay, Agathe; Jurek, Lucie (Frontiers in Psychology, 2025)
BackgroundAutism Spectrum Disorder (ASD) presents early communication and social challenges, necessitating timely and accessible intervention. Pre-school Autism Communication Therapy (PACT), a parent-mediated intervention, empowers parents to facilitate their child’s development. However, accessibility issues often hinder families from accessing evidence-based intervention. This pilot study assessed the feasibility of videoconferencing-based PACT as a precursor for a multicenter randomized controlled trial.MethodologyA mixed-methods approach integrated quantitative retrospective measures and semi-structured interviews. Participants included children diagnosed with ASD who received PACT, and PACT-trained professionals with videoconferencing experience. Feasibility was assessed through audio and video quality, internet stability, and session length. Professionals’ experiences were analyzed using a qualitative thematic analysis. Autism severity, parent–child interaction, and therapeutic changes were also described.ResultsNine parent–child dyads and eight PACT therapists were included in the study. Videoconferencing-based PACT intervention proved feasible, with 95.1% of the 41 sessions rated as feasible on the scale. Technical challenges such as audio quality (7.3%) and screen sharing (19.1%) have emerged, which therapists circumvented to maintain intervention quality. Autism severity and parent–child interaction showed positive trends, supported by qualitative findings reporting increased parental confidence and enhanced synchrony. The core components of PACT were successfully adapted to the remote setting.ConclusionThis pilot study suggests that delivering PACT via videoconferencing is a feasible approach to enhance the accessibility of evidence-based interventions for ASD. Larger-scale research with rigorous controls is required to validate these promising findings. An ongoing multicenter randomized trial aims to address this gap.